IMPROVING STUDENT WRITING SKILLS IN INDONESIAN LANGUAGE LEARNING NARRATIVE WRITING MATERIALS USING WRITING PROCESS APPROACH - Mariana, Ina; Purnomo, Sidik; Firdaus, Anugrah Ramadhan (COLLASE (Creative of Learning Students Elementary Education), 2018)
This research is motivated by the teacher's lack of getting students to write, and the teacher is not right in determining the approach to train students to write. While the problems that arise from students include the low ability of students to write, especially in learning to write essays. The problems are characterized by (1) the low ability of students to write stories chronologically so that they become complete essays, (2) the low ability of students to integrate relationships between sentences, and (3) the low ability of students in the use of spelling and punctuation in essays. Research methods use quantitative. this study uses a qualitative approach with classroom action research design. To obtain data in the context of research, researchers used three ways of collecting data, namely by using interviews, observation and documentation. The study was conducted for 1 month, from January 8 2018 to January 31 2018. The results of the research and discussion showed that the students' ability in writing narrative essays and student writing skills through the approach to writing process is very appropriate so that it can produce a good character.